SOME ASPECTS OF PROFESSIONAL AND PSYCHOLOGICAL SELECTION IN THE ARMED FORCES OF UKRAINE - Bespalko, A.; Lelyuk, M. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2022)
An analysis of some aspects of professional and psychological selection in the Armed Forces of Ukraine is presented. The diagnosis of social, psychological, psychophysiological, psychomotor qualities and physiological reserves of the bodies of candidates for service is generalized. The order, mechanisms, and methodological basis of professional selection in the Armed Forces have been determined. Systematized the requirements for educational activities in higher military educational institutions (military training units of higher education institutions) (HMEI) (MTUHEI) of Ukraine and professional activities in the Armed Forces of Ukraine. The structure of the individual and psychological characteristics of the candidate for training, which he must have in order to successfully master the profession and fulfil his professional and service duties, is highlighted. Modern professional psychological selection is considered as a complex scientific problem, on the one hand, as a system, on the other – as a process. The stages of psychological selection based on a systematic approach have been supplemented and detailed. Recommendations are given for improving the comprehensive program of professional and psychological selection, increasing the effectiveness of the system of professional psychological selection of candidates for military service under contract and for training at the HMEI (MTUHEI) (creating a standardized systematic approach to psychological selection in the Armed Forces, studying professionally important qualities, indications and contraindications for service, development of professional profiles (acmeograms) of military specialists, adequate selection methods with various candidate criteria and formation of the most informative test psychodiagnostic batteries for studying and determining individual psychological characteristics of the personality, forecasting the development of mental processes and states in relation to the conditions and requirements of future activities in various military specialties, implementation of the automated systems for staffing military units at various stages of selection).
Keywords: professional selection, professional-psychological selection, psychophysiological selection, military personnel, systematic approach to psychological selection in military personnel